“DIVERSIDADE É A SENTENÇA” : CONTRIBUIÇÕES DOS MOVIMENTOS FEMINISTAS E MOVIMENTO LGBTQ+ NO RECONHECIMENTO DA DIVERSIDADE HUMANA (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
Contemporary society, which should value diversity, is increasingly faced with the lack of identity recognition within social relationships, which contributes to the inferiorization of different groups due to their physical, optional, sexual, cultural, etc. . With regard to the manifestations of sexuality, those that do not fit the molds determined to be correct by heteronormativity are objects of great controversy in the social environment. Thus, through a hypothetical deductive study, the research seeks to analyze the contributions of feminist movements and LGBTQ + movements in the process of recognizing human diversity. The study demonstrates that, although distinct and complex, the Feminist and LGBTQ + Movements have more points in common than they seem to perceive and accumulate a reserve of power that can be explored creatively in a joint and partner way in the search for dignity, citizenship, justice, equality and rights, so much so that they are protagonists of social pressure that created legislation aimed at the social and legal recognition of human diversity.